E-MODULE BASED PROJECT LEARNING FOR TEACHING SPEAKING - Diyah Dwi Agustina; Ahmad Efendi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
In this digital era, e-module becomes a great help in accessing knowledge combined with the good method application. This study is intended to develop an e-Module design based on Project Learning in the Speaking for General Communication course. This e-Module Project Based Learning is designed with the purpose of creating effective and efficient learning. The subjects of this study were students in 2nd semester of the English Education study program. The kinds of this research are a Research and Development (R&D) research and the method used is ADDIE development method (Analysis, Design, Development, Implementation and Evaluation). The stages in this study are the needs analysis stage, the e-module planning and design stage, the e-module development stage, the e-module implementation stage and the evaluation and revision stage of the module. The research used descriptive qualitative and quantitative descriptive methods. Through the project designed in the e-module, it is hoped that it will increase student creativity and increase student activity in speaking. Furthermore, students' speaking skills can be improved.